2002
DOI: 10.1067/mhn.2002.129731
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ankyloglossia on Speech in Children

Abstract: Tongue mobility and speech improve significantly after frenuloplasty in children with ankyloglossia who have articulation problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
115
1
22

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(142 citation statements)
references
References 7 publications
4
115
1
22
Order By: Relevance
“…For children over the age of 1 or 2 years, a frenuloplasty, a more extensive procedure requiring closure of the wound with absorbable sutures, is considered more appropriate to allow for additional tongue-tie release and to minimize scarring. The efficacy of these procedures in increasing latching time, reducing maternal breastfeeding pain [10], enhancing articulation [11], and improving dental health and development [12] has been well-described and underscores the important role of tongue-tie release in pediatric development.…”
Section: Discussionmentioning
confidence: 99%
“…For children over the age of 1 or 2 years, a frenuloplasty, a more extensive procedure requiring closure of the wound with absorbable sutures, is considered more appropriate to allow for additional tongue-tie release and to minimize scarring. The efficacy of these procedures in increasing latching time, reducing maternal breastfeeding pain [10], enhancing articulation [11], and improving dental health and development [12] has been well-described and underscores the important role of tongue-tie release in pediatric development.…”
Section: Discussionmentioning
confidence: 99%
“…15 patients were available for postoperative review of whom 9 demonstrated improvement on speech and language assessment, 2 had ongoing problems and 4, who had normal preoperative assessments, were unchanged. Overall average parental perception of speech intelligibility improved from 3.4 to 4.2 out of 5 [34].…”
Section: Effect On Speech Developmentmentioning
confidence: 93%
“…44,45 Initial symptoms of ankyloglossia include maternal nipple pain with breastfeeding, loss of suction or a clicking sound while feeding, and poor latch. 46,47 On examination, there is a frenulum inserted near the tip of the tongue, inability to extend the tongue to the lips or to the roof of the mouth, and notched or heart-shaped tongue on extension. Although interference with breastfeeding is the most common sequela, significant ankyloglossia is also associated with articulation difficulty, 45 but not delay in onset of speech.…”
Section: Sensory Developmentmentioning
confidence: 98%
“…Although interference with breastfeeding is the most common sequela, significant ankyloglossia is also associated with articulation difficulty, 45 but not delay in onset of speech. 46 Difficulty with oral hygiene increases the risk of dental caries and periodontal disease. Inability to lick and perform other activities that require tongue extension may have social consequences.…”
Section: Sensory Developmentmentioning
confidence: 99%